Numerical Study of Non-Premixed Combustion Characteristics on Supplementary Firing of HRSG - Ariwibowo, Teguh Hady; Ghani Safitra, Arrad; Haidar Fakr, Muhammad; Aghist Fitrony, Muhammad (Eksergi, 2022)
Computational fluid dynamics (CFD) is a simulation model to provide complex processes in the industry that has been widely used to investigate industrial-scale combustion phenomena. Supplementary firing is used to increase steam production. The non-premixed combustion is a type of supplementary firing. Supplementary firing has seven burners arranged vertically. Supplementary firing uses exhaust steam from a gas turbine to ignite the air. This research investigates the combustion characteristics of flame length and exhaust gas emission at burners. The viscous model was observed by using non-premixed modeling. While the absorption of radiation in the combustion residual gas was observed by using the weight sum-gray gases model (WSGGM). This study used the realizable k-Îµ model and tetrahedron meshing algorithm to approach the turbulent characteristics. The total nodes and the orthogonal mesh quality in the meshing steps are 1,334,359 and 0.86, respectively. The modeling results show that burners-1 and 7 have longer flame compared to other burners. The combustion exhaust gas has height contents of CO2 and H2O. The velocity near the furnace wall is lower than the center of the furnace, but the pressure is higher. This phenomenon is dominantly influenced by the thermal boundary layer.